The secret lives of numbers numerals and their peculiarities in mathematics and beyond - Posamentier, Alfred S. (Prometheus Books, an imprint of Globe Pequot, the trade division of The Rowman & Littlefield Publishing Group, Inc., 2022)
"The Secret Lives of Numbers takes readers on a journey through integers, considering their numerological assignments as well as their significance beyond mathematics and in the realm of popular culture"--